The Reality of the Prevailing Organizational Culture in the Palestinian Public Schools in Jerusalem from the Teachers' Point of View - Tamimi, Souhail (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to identify the reality of the prevailing organizational culture in the Palestinian public schools in Jerusalem. Methods: The analytical descriptive approach was utilized in the study, and a questionnaire of (20) items was created as a tool for gathering primary data on the variables. A simple random sample of (282) male and female teachers was given the questionnaire. Results: The study's findings revealed that the reality of the dominant organizational culture in Palestinian public schools in Jerusalem, as perceived by instructors, was quite high. The results also showed statistically significant differences attributed to the variable of years of service, with the differences favoring less than five years of service. However, no statistically significant differences were attributed to the variables of gender, educational qualification, and school level. Conclusions: The study recommends incorporating organizational culture principles into programs to develop the professional performance of school principals and maintaining the high level of organizational culture that exists in Palestinian public schools in Jerusalem by holding training courses for school principals to inform them of the most recent educational developments, provide the necessary support, and promote the rights of teachers in public schools in Jerusalem.